(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study was to describe the applicability of correlation, multiple regression procedure, ANOVA and t-test have been applied to raw data of incidence of average thrips’ population on garlic crop. The data was collected from the Department of Entomology, J.N.K.V.V., Jabalpur (M.P.) in Kharif season 2011-12, 6 transplanting dates (1 st November2012,15 th November2012, 1 st December2012,15 th December2012, 1 st January2012,15 th January2012).The multiple regression procedure has been applied to study the pattern of seasonal fluctuations of garlic thrips through prediction models at different transplanting periods. Maximum temperature, vapor pressure, relative humidity, wind speed, evaporation and rainfall played an important role for governing the garlic thrips population at different of transplanting dates. At On 1 stNovember Trans planting date thrips population was significantly and positivelycorrelated with maximum temperature and evaporation while the other correlations were found to be non-significant.ANOVA was showing a combination of X1(Maximum Temperature) and X4(Rainfall) giving the value of R2 as 75% towards the prediction of the thrips population.